The Instagram Effect on Tourist Destination Choices: Unveiling Key Attraction Elements - Beni Ismarizal; Ahmad Hudaiby Galih Kusumah (Journal of Consumer Sciences, 2023)
Social media is a significant communication tool in the tourism industry because it can reach a wide audience, interact directly, and is very effective in promoting tourist destinations and building close relationships between tourism businesses and tourists. Nonetheless, the role of social media in tourists' decision-making to visit a tourist destination is still not fully understood. Therefore, this study aims to understand what elements of Instagram content can make tourists decide to visit a tourist destination. Data collection was carried out using in-depth interviews with 20 domestic tourists. The analytical technique used to achieve the research objectives consisted of two steps, namely thematic analysis and followed by qualitative descriptive analysis. Based on the results of this study showed to be that Instagram content can trigger Generation Y and Z tourists' decisions to visit tourist destinations. Interesting Instagram content in terms of color, captions, and other people's comments can be one of the factors that attract tourists to visit tourist destinations. Overall, the research presents valuable insights for social media stakeholders and marketers in the tourism industry to optimize their content strategy and effectively target and engage Generation Y and Z tourists. However, it should be noted that these studies may have limitations in the scope and population studied, so further research is needed to deepen and expand our understanding of how Instagram affects Y and Z-generation travel decisions.